Speech improvement lessons on the front vowels for Laguna Tagalog learners of English - Javier, Lourdes Zaide 1926- (publisher not identified], 1965)
An observation of the prevailing speech difficulties among high school students of the Southern Tagalog Region, particularly of Sta. Cruz, Laguna, reveals the distortions in learning the vowel sounds of the English language. This problem arises from the differences in the patterning of our vowel phonemes from those of the English vowel phonemes. Our students tend to shift from one vowel to another.